РЕЦЕПЦИЈА И АДАПТАЦИЈА НА РАСКАЗОТ „ВАМПИР“ НА ПЕТРЕ М. АНДРЕЕВСКИ ВО СЛОВЕНИЈА (Philological Studies, 2019)
After the Slovenian translation of the short story "The Vampire" written by Macedonian writer Petre M. Andreevski was published and recorded for the radio, it was also adapted (transformed) into another genre and performed by a group of Slovene artists. The first part of the paper contains information about the published and recorded translations of the poetry and prose of Petre M. Andreevski into Slovenian, whereas the second is focused on the adaptation of the story "The Vampire“ by Ana Dusha. Her version puts Andreevski’s text in a new, fresh and exciting context.
Keywords: Macedonian literature, Petre M. Andreevski, translation, intercultural mediation, literary adaptation